2009
DOI: 10.1074/jbc.m109.036848
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanism of Matrix Metalloprotease-2 Enzymatic Activity by Factor Xa and Thrombin

Abstract: Matrix metalloprotease (MMP)-2 plays a key role in many biological and pathological processes related to cell migration, invasion, and mitogenesis. MMP-2 is synthesized as a zymogen that is activated through either a conformational change or proteolysis of the propeptide. Several activating enzymes for pro-MMP-2 have been proposed, including metalloproteases and serine proteases. The mechanism of pro-MMP-2 activation by metalloproteases is well established, and the most studied activation mechanism involves cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…In our previous study using metalloprotease inhibitors and pro-MMP-2 mutants incapable of cleavage by MT1-MMP, we showed MT1-MMP-independent activation of pro-MMP-2 by thrombin (26). We further demonstrated that thrombin cleaved the propeptide on the C-terminal side of Arg 98 and Arg 101 followed by intermolecular autoproteolytic cleavage at the Asn 109 -Tyr peptide bond for full enzymatic activity (26). In addition to its role in activation, thrombin also degraded MMP-2, but this degradation was reduced greatly under cell-associated conditions with a concomitant increase in activation (26).…”
Section: Matrix Metalloprotease 2 (Mmp-2)mentioning
confidence: 99%
“…In our previous study using metalloprotease inhibitors and pro-MMP-2 mutants incapable of cleavage by MT1-MMP, we showed MT1-MMP-independent activation of pro-MMP-2 by thrombin (26). We further demonstrated that thrombin cleaved the propeptide on the C-terminal side of Arg 98 and Arg 101 followed by intermolecular autoproteolytic cleavage at the Asn 109 -Tyr peptide bond for full enzymatic activity (26). In addition to its role in activation, thrombin also degraded MMP-2, but this degradation was reduced greatly under cell-associated conditions with a concomitant increase in activation (26).…”
Section: Matrix Metalloprotease 2 (Mmp-2)mentioning
confidence: 99%
“…Many reports suggest that thrombin regulates the gelatinolytic activity of MMP-2 and MMP-9 in cancer cell invasion [7][8][9][10]35]. However, the effect of thrombin on human oral squamous carcinoma cells is not fully understood.…”
Section: Resultsmentioning
confidence: 99%
“…Expression Plasmids and Site-directed Mutagenesis-Plasmids for expression of full-length MMP-2 or MMP-2 with C-terminal Myc and His tags were described previously (7). To make an expression plasmid encoding hemopexin-like domaindeleted pro-MMP-2, site-directed mutagenesis was used to convert Pro 466 to a stop codon using a mutagenesis kit (iNtRON Biotechnology, Kyungki-Do, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, we demonstrated that thrombin directly cleaved the propeptide on the C-terminal side of Arg 98 and Arg 101 with a preference for Arg 101 ; this was followed by intermolecular autoproteolytic cleavage at the Asn 109 -Tyr peptide bond, resulting in full enzymatic activation (7). We further showed that heparan sulfate was required for thrombin-mediated activation of pro-MMP-2 (25).…”
mentioning
confidence: 99%